2014
DOI: 10.4236/ce.2014.53023
|View full text |Cite
|
Sign up to set email alerts
|

Creativity & Innovation: Four Key Issues from a Literature Review

Abstract: This paper is about creativity and innovation in the educational field. Through a literature review, we describe the results of two decades of research on creativity and innovation in the educational and organizational field, to underline what seemed to work and what did not, to enable these processes function effectively. In this literature review, a search of publications dealing with the issues of innovation and creativity and the links between these two issues has been made. We decided to put these studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…These observations are considered by the research team to be an opportunity to focus on providing training and awareness program to students especially in creativity and innovation tools and techniques such as those described by the American society of Quality in the reference book by (Keathly, Merrill, Owens, Meggarrey, & Posey, 2014). It is worth mentioning here that, as pointed out recently by (Pisanu & Menapace, 2014), the use of creative thinking techniques such brainstorming, lateral thinking, mind-mapping, six thinking hats technique, morphological analysis, can improve substantially the existing levels of creativity and innovation among individuals in organizations.…”
Section: Parents Educational Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are considered by the research team to be an opportunity to focus on providing training and awareness program to students especially in creativity and innovation tools and techniques such as those described by the American society of Quality in the reference book by (Keathly, Merrill, Owens, Meggarrey, & Posey, 2014). It is worth mentioning here that, as pointed out recently by (Pisanu & Menapace, 2014), the use of creative thinking techniques such brainstorming, lateral thinking, mind-mapping, six thinking hats technique, morphological analysis, can improve substantially the existing levels of creativity and innovation among individuals in organizations.…”
Section: Parents Educational Levelmentioning
confidence: 99%
“…An extensive literature review on creativity and innovation in the educational field was presented by (Pisanu & Menapace, 2014). Based on the review of the technical literature, they have identified four main key dimensions to enhance creativity and innovation within organizations and to build a practical framework that can serve as guidelines to a better understanding of, the creative process that leads to the stabilization of the innovation within educational systems.…”
Section: Research Framework and Questionsmentioning
confidence: 99%
“…It is worth mentioning here that, as pointed out recently by (Pisanu and Menapace, 2014), the use of creative thinking techniques such as brainstorming, lateral thinking, mind-mapping, six thinking hats technique, morphological analysis, can improve substantially the existing levels of creativity and innovation among individuals in organizations, including higher education institutions.…”
Section: Q10mentioning
confidence: 91%
“…An extensive literature review on creativity and innovation in the educational field was presented by (Pisanu and Menapace, 2014). Based on the review of the technical literature, they pointed out four main key dimensions to enhance creativity and innovation within organizations and to build a practical framework that can serve as guidelines to a better understanding of the creative process that leads to the stabilization of the innovation within educational systems.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Also, innovation is mostly viewed as 'use of technology itself'. Pisanu and Menapes [20] clears the confusion by putting forward that innovation in education is needed to incorporate old and new technologies and educational environments that already exist may be adapted and upgraded through the use of technology.…”
Section: Introductionmentioning
confidence: 99%